If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-3)+5=3(x-1)
We move all terms to the left:
4(x-3)+5-(3(x-1))=0
We multiply parentheses
4x-(3(x-1))-12+5=0
We calculate terms in parentheses: -(3(x-1)), so:We add all the numbers together, and all the variables
3(x-1)
We multiply parentheses
3x-3
Back to the equation:
-(3x-3)
4x-(3x-3)-7=0
We get rid of parentheses
4x-3x+3-7=0
We add all the numbers together, and all the variables
x-4=0
We move all terms containing x to the left, all other terms to the right
x=4
| 3v+(-12v)+8v+(-14v)-(-14v)=18 | | 2(w+12)(w-10)=0 | | 3(1+2n)-9=6n-6 | | 13m+2m-13m-m+2=7 | | (7x+17)+90+(3x+13)=180 | | 3.5/4+9=x | | -17j+10j=-14 | | 7u-u-(-15u)-18u+(-11u)=(-16) | | x/2/1/3=1 | | p-4+3=5 | | 5h-10=3h+32 | | 12x-15=15-3x | | 6.8=x+2.3 | | (-16m)-(-11m)+(-20m)+m-(-17)=(-7) | | -6x+22=-4x+14 | | p-6+7=2 | | e+1.2=-2 | | 5x+5=53 | | 1x+15=22 | | 7w+3=10 | | 3+3x=43 | | 9q+2q+4q-15q+3q=18 | | 2x+2x+3x+27+11=180 | | 3.5/x+9=23 | | 1x37=39 | | 5x+6x-6x=5 | | 9=6y+51 | | 13c+(-19c)=12 | | 9z+5z-9z+4z=18 | | 5x+3=15-7x | | –11=3f+7 | | 2x=5^3 |